Troubling truth and reconciliation in Canadian education : critical perspectives - Styres, Sandra D., 1961-; Kempf, Arlo (Edmonton, Alberta, Canada : University of Alberta Press, 2022)
"Troubling Truth and Reconciliation in Canadian Education offers a series of critical perspectives concerning reconciliation and reconciliatory efforts between Canadian and Indigenous peoples. Indigenous and non-Indigenous scholars address both theoretical and practical aspects of troubling reconciliation in education across various contexts with significant diversity of thought, approach, and socio-political location. Throughout, the work challenges mainstream reconciliation discourses. This timely, unflinching analysis will be invaluable to scholars and students of Indigenous studies, sociology, and education. Contributors: Daniela Bascuñán, Jennifer Brant, Liza Brechbill, Shawna Carroll, Frank Deer, George J. Sefa Dei (Nana Adusei Sefa Tweneboah), Lucy El-Sherif, Rachel yacaaʔał George, Celia Haig-Brown, Arlo Kempf, Jeannie Kerr, Ruth Green, David Newhouse, Amy Parent, Michelle Pidgeon, Robin Quantick, Jean-Paul Restoule, Toby Rollo, Mark Sinke, Sandra D. Styres, Lynne Wiltse, Dawn Zinga."--
Theoretical perspectives on (lr)reconciliation: Polishing the silver covenant chain -- Reconceptualizing reconciliation in education: Teaching and learning in right relation.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Critical pedagogy -- Canada; Transformative learning -- Canada; Culturally relevant pedagogy -- Canada; Culturally sustaining pedagogy -- Canada; Indigenous peoples -- Education -- Canada; Indigenous peoples -- History -- Study and teaching -- Canada; Reconciliation -- Study and teaching -- Canada; Canada -- Race relations -- Study and teaching; Canada -- Ethnic relations -- Study and teaching; Pédagogie critique -- Canada; Apprentissage transformateur -- Canada; Pédagogie culturellement adaptée -- Canada; Réconciliation -- Étude et enseignement -- Canada; SOCIAL SCIENCE / Indigenous Studies; Critical pedagogy; Culturally relevant pedagogy; Culturally sustaining pedagogy; Ethnic relations -- Study and teaching; Indigenous peoples -- Education; Indigenous peoples -- Study and teaching; Race relations -- Study and teaching; Reconciliation -- Study and teaching; Transformative learning; Canada; Indigenous education TRC reconciliation residential school teacher student settler Indigenizing Indigenize decolonizing decolonize antiracism anti-racism white supremacy whiteness social justice university high school; Electronic books; History